PENGEMBANGAN PRODUK BERBASIS TEBU: STUDI INOVASI PRODUK DI PT KREBET MALANG - Mahbobi; Aziz Azhari; Marsidi; Mohammad Romzi; Mohammad Ricki; Mohammad Rosidi (STAI AN-NAJAH INDONESIA MANDIRI, 2023)
Abstract: The production of pepper in Malang district is quite abundant. It's not offset by the means of turning cabbage into sugar. There are two sugar factories in Malang district, the Big Kebon sugar plant and the Krebet sugar plant. But these two factories are still not enough to turn beet into sugar, so that the rest are shifted to other districts. Besides, the disappearance of the old building character of the factory replaced with a building far from the original became a problem to be solved. The Krebet Sugar Factory is the only remaining Dutch colonial remnant in the poor southern region. This plant has many shortcomings that need to be fixed in order to function properly. However, this plant also has advantages that can still beined or re-developed to be much better. The revitalization of the Sugar Krebet Malang plant area aims to address the problems that arise today based on the plant design standards and the theme of Historicism. Both are expected to remedy the current shortage, thus acquiring a new sugar plant area that can accommodate all the needs that are currently not met. Keywords: Product Development, Bags, Innovation References Armstrong, D. M. (2004). Truth and truthmakers. Cambridge University Press. Dewi, N. K., & SE, G. A. (2012). Pengaruh iklan, citra merek, dan kepuasan konsumen terhadap loyalitas konsumen dalam menggunakan vaseline hand and body lotion di kota Padang (studi kasus di PT. Unilever cabang padang). Sumber, 6(1), 26. Hermawan, A. F., Supeni, R. E., & Rozi, A. F. (2018). Pengaruh Kualitas Produk, Harga dan Promosi terhadap Keputusan Pembelian Konsumen Sepeda Motor Honda Beat di Dealer MPM Motor Kalisat-Jember. Jurnal Manajemen Dan Bisnis, Xv Nomor, 2. PORUMB, A. T., BOGDAN, R., SĂCARA-ONIŢA, A., & PORUMB, C. (2022). TYPES DE RÉMUNÉRATION DU TRAVAIL INDÉPENDANT (ÉTUDE COMPARATIVE FRANÇAIS-ROUMAIN). Annals of the University of Oradea, Economic Science Series, 31(1). Romadhoni, R. H. A. (2021). Pengaruh service quality terhadap customer satisfaction dan brand loyalty telkomsel: Studi pada pengguna Telkomsel di Kota Malang (Doctoral dissertation, Universitas Islam Negeri Maulana Malik Ibrahim). Sanjaya, D., Haryanto, A., dan Tamrin. 2014. Produksi Biogas dari Campuran Kotoran Sapi dengan Kotoran Ayam. Jurnal Teknik Pertanian Lampung, Vol. 4, No. 2, hal: 127-136 Sari, Siti Nita Ratna Sari, Pendirian Pabrik Gula Krebet Dan Dampaknya Terhadap Masyarakat Kabupaten Malang (1906-1945), Diploma Theis, Universitas Negeri Malang. 2021. Sari, Siti Nita Ratna Sari, Pendirian Pabrik Gula Krebet Dan Dampaknya Terhadap Masyarakat Kabupaten Malang (1906-1945), Diploma Theis, Universitas Negeri Malang. 2021 Solihin, I., Putra, R. T., Salamah, N. S., Fidya, E. S., & Khairunnisaa, L. A. (2020). The Effect of the Implementation of Indonesian Sustainable Palm Oil (ISPO) on the Average Export Value of Indonesian Crude Palm Oil (CPO) to the Netherlands and Italy during the 2012-2017 Period. Umar, H. (2014). Faktor-faktor yang memengaruhi loyalitas pelanggan pada penerbangan low cost carrier. Jurnal Manajemen Transportasi & Logistik (JMTransLog), 1(2), 127-138. Windyasmara, L., Pertiwiningrum, A., dan Yusiati, L.M. Pengaruh Jenis Kotoran Ternak Sebagai Substrat dengan Penambahan Serasah Daun Jati (Tectona grandis) Terhadap Karakteristik Biogas pada Proses Fermentasi. Buletin Peternakan, Vol. 36 No. 1, hal: 40-47. Februari 2012 Wulandari, A., & Nursiam, M. H. (2013). Pengaruh Pertumbuhan Ekonomi, Pendapatan Asli Daerah (PAD) Dan Dana Alokasi Umum (DAU) Terhadap Belanja Modal (Studi Kasus Di Kabupaten Sragen Tahun Anggaran 2003-2011) (Doctoral dissertation, Universitas Muhammadiyah Surakarta). Zuliyana, Wirawan, S.K., Budhijanto, W., dan Cahyono, R.B. 2015. Pengaruh Kadar Air Umpan dan Rasio C/N pada Produksi Biogas dari Sampah Organik Pasar. Jurnal Rekayasa Proses, Vol. 9, No. 1, hal: 22-27.